2020
DOI: 10.3389/fmed.2020.566582
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Effects of the N-Methyl-D-Aspartate Receptor Antagonist Kynurenic Acid and the Synthetic Analog SZR-72 on Microcirculatory and Mitochondrial Dysfunction in Experimental Sepsis

Abstract: Introduction: Sepsis is a dysregulated host response to infection with macro- and microhemodynamic deterioration. Kynurenic acid (KYNA) is a metabolite of the kynurenine pathway of tryptophan catabolism with pleiotropic cell-protective effects under pro-inflammatory conditions. Our aim was to investigate whether exogenously administered KYNA or the synthetic analog SZR-72 affects the microcirculation and mitochondrial function in a clinically relevant rodent model of intraabdominal sepsis.Methods: Male Sprague… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 47 publications
0
26
0
1
Order By: Relevance
“…The animals were randomly divided into sham-operated (n ∑ =15) and septic groups (n ∑ =62). Polymicrobial sepsis was induced with intraperitoneally (ip)-administered fecal inoculum, as described before ( 17 , 26 ). Briefly, fresh feces samples were randomly collected from healthy rats (n=4–5), suspended and incubated in physiological saline (37°C, 5h).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The animals were randomly divided into sham-operated (n ∑ =15) and septic groups (n ∑ =62). Polymicrobial sepsis was induced with intraperitoneally (ip)-administered fecal inoculum, as described before ( 17 , 26 ). Briefly, fresh feces samples were randomly collected from healthy rats (n=4–5), suspended and incubated in physiological saline (37°C, 5h).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to glutamate receptor antagonism, KYNA acts as an agonist for G protein-coupled receptor GPR35 and the aryl hydrocarbon receptor and regulates glutamatergic neurotransmission and immune activation (25). Previously, we have already shown that KYNA and its synthetic analogue, termed SZR-72, ameliorated sepsis induced mitochondrial dysfunction (decreased oxygen consumption and DYmt) in the rat liver (17). Nevertheless, the mitochondrial effects of these compounds in the CNS have not been examined before.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that KYNA could only poorly cross the BBB, while SZR-72 is BBB-permeable due to a water-soluble side chain with an extra cationic center ( 9 , 18 , 21 ). Furthermore, a facilitated membrane crossing of SZR-72 is suspected, which could influence intracellular signaling, including the activation of antioxidative and anti-apoptotic pathways ( 22 ). On the other hand, a distinct binding to the glycine site of the NMDA receptor has a higher affinity to SZR72 than KYNA ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a facilitated membrane crossing of SZR-72 is suspected, which could influence intracellular signaling, including the activation of antioxidative and anti-apoptotic pathways ( 22 ). On the other hand, a distinct binding to the glycine site of the NMDA receptor has a higher affinity to SZR72 than KYNA ( 22 ).…”
Section: Introductionmentioning
confidence: 99%